THE GASTRODIPLOMACY: INDONESIA’S CULINAIRY PUBLICITY IN THE NETHERLANDS - Marsha Huwaidaa (Asosiasi Dosen Muda Indonesia, 2022)
Indonesia has a different diplomatic relationship with the Netherlands, based on post-colonialism resulting in thick cultural acculturation and close bilateral relations. The various events have become an accumulation of ties between the two countries, thus harming the Dutch people's perception of Indonesia and vice versa. Therefore, Indonesia launched a public diplomacy program through gastro diplomacy. Gastro diplomacy was chosen as the object of research because of Indonesian cuisine's progressive potential, which has been selected as a positive impact on bilateral relations and as a medium for promoting Indonesia in the Netherlands. The researcher will use the qualitative method in this study. The research procedure carried out gave descriptive data results whose results were examined through speech or writing from the behavior of the observed person. The purpose of this research analysis is to describe the implementation of Indonesian gastro diplomacy in the Netherlands through the embassy program, explain gastro diplomacy in general, and identify opportunities for Indonesia to take advantage of culinary arts as an instrument of public diplomacy